2004
DOI: 10.1002/ejoc.200400358
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of two Conformationally Restricted Piperazine Scaffolds for Combinatorial Chemistry

Abstract: Piperazines are widely used as central elements in the construction of bioactive molecules. Herein, the short synthesis of two chiral 2,6‐bridged piperazines possessing orthogonally stable protecting groups from readily available starting materials is described. It is suggested that these molecules may be used as conformationally restricted scaffolds for the combinatorial synthesis of drug‐like compounds. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…[4] C-Substituted piperazines are contained in several pharmacologically active compounds such as platelet activating factor (PAF) inhibitors, [5] soluble epoxide hydrolase (sEH) inhibitors, [6] farnesyl transferase inhibitors (i.e., L-745631), [7] and NK-1 antagonists (i.e., FK-355). [8] As part of our efforts working toward the synthesis of novel scaffolds with high potential as building blocks in medicinal chemistry, we became interested in 1-benzyl-2-difluoromethyl-piperazine (1), hypothesizing that modulation of N-atom electronic as well as steric hindrance properties could be valuable strategies to modulate activity at the biological target and influence physicochemical properties (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[4] C-Substituted piperazines are contained in several pharmacologically active compounds such as platelet activating factor (PAF) inhibitors, [5] soluble epoxide hydrolase (sEH) inhibitors, [6] farnesyl transferase inhibitors (i.e., L-745631), [7] and NK-1 antagonists (i.e., FK-355). [8] As part of our efforts working toward the synthesis of novel scaffolds with high potential as building blocks in medicinal chemistry, we became interested in 1-benzyl-2-difluoromethyl-piperazine (1), hypothesizing that modulation of N-atom electronic as well as steric hindrance properties could be valuable strategies to modulate activity at the biological target and influence physicochemical properties (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The piperazine ring is a common structural motif and pharmacophore found in a large number of drugs [1–3]. Piperazine derivatives can be used as main structure or substituent of the drugs to obtain the desired pharmacological activity or pharmacokinetic activity, they also can be served as building blocks commonly used in the synthesis of pharmaceutically active substances [4].…”
Section: Introductionmentioning
confidence: 99%
“…The piperazine scaffold not only is a very useful building block in coordination polymers and fine industrial chemicals, , but it is also an important pharmacophore found in a large number of biologically active compounds. Amine- and alcohol-extended piperazines have considerably extensive applications in the preparation of hardeners of epoxy resins, corrosion inhibitors, insecticides, accelerators for rubber, urethane catalysts, and antioxidants. , 1-(2-Aminoethyl)piperazine is used as intermedia of nonviral gene delivery vectors . Recently, piperazine derivatives have even been developed as CO 2 capturing materials…”
Section: Introductionmentioning
confidence: 99%